2009
DOI: 10.1051/limn/2009031
|View full text |Cite
|
Sign up to set email alerts
|

Species abundance distribution of benthic chironomids and other macroinvertebrates across different levels of pollution in streams

Abstract: -Chironomid assemblages collected from seven different streams in South Korea were investigated. The subfamily composition of chironomids was clearly differentiated accross different levels of organic pollution. Species abundance distributions (SADs) of chironomid communities were compared with the total macroinvertebrate communities across different levels of pollution. The number of species with minimal range of abundance was lower in SADs for chironomid communities compared with total communities. The log n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 51 publications
0
27
0
1
Order By: Relevance
“…Various parameters of these models (e.g., k values in the geometric series, a and γ values in the log-normal distribution) have been used as indicators for community structure [28,49,50]. In this study, we extended the scope of RADs so that it would offer more information on community structure [21,27].…”
Section: Community Patterns and Indicator Speciesmentioning
confidence: 99%
“…Various parameters of these models (e.g., k values in the geometric series, a and γ values in the log-normal distribution) have been used as indicators for community structure [28,49,50]. In this study, we extended the scope of RADs so that it would offer more information on community structure [21,27].…”
Section: Community Patterns and Indicator Speciesmentioning
confidence: 99%
“…While community parameters (i.e., diversity, similarity) provide only limited information on community as single indices, SADs can provide information on the structure property of communities using two dimensions on rank and abundance of species. Since Raunkiaer (1909) and Motomura (1932) first used SAD to evaluate structures of communities, a large number of studies on SAD have been reported on various taxa including terrestrial plants (Forster and Warton, 2007), terrestrial animals (Ford and Lancaster, 2007) and freshwater macroinvertebrate communities (Qu et al, 2008;Tang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to marine benthic communities, variation in the log normal distribution in SADs was reported when detecting pollution induced changes, towards a geometric series (Gray and Mirza, 1979). SADs have been further dealt in revealing the states of communities of benthic macroinvertebrates in fresh water across different levels of pollution (Qu et al, 2008;Tang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…СОМ се прво користио за одређивање просторне и временске дистрибуције бентосних заједница макроинвертебрата (Chon et al, 1996). Од тада велики број аутора користи СОМ за ординацију и класификацију, предикцију и моделовање података у различитим аспектима истраживања бентосних макроинвертебрата (Chon et al, 2000;Verdonschot, 2005;Tang et al, 2010;Chon, 2011). СОМ анализа је такође била коришћена за моделовање динамике ларви хирономида на различитим профилима станишта .…”
Section: методе узорковања и идентификацијеunclassified
“…The SOM was first used in pattering the benthic community by Chon et al (1996). Since then, many authors have used SOM for clustering, classification, estimation, prediction, and data mining in various aspects of benthic macroinvertebrate research (Chon et al 2000;Verdonschot 2005;Tang et al 2010;Chon 2011). The SOM has also been used for the analysis of chironomid assemblages in various habitats and for the presentation of the assemblage patterns .…”
mentioning
confidence: 99%